The Impact of Blockchain Technology in Higher Education Quality Improvement - Riya Widayanti; Eka Purnama Harahap; Ninda Lutfiani; Fitra Putri Oganda; Ita Sari Perbina Manik (Jurnal Ilmiah Teknik Elektro Komputer dan Informatika, 2021)
The times have made technology increasingly developed that there are innovations as new media to make it easier for humans in everyday life. Blockchain technology is an innovation that has been applied in various fields such as education, health, economy, and other areas. In this study, researchers want to see the impact that blockchain technology has had on universities in technology and information to improve universities' quality. The methodology used is by reviewing previous research papers related to the research. So that this research is expected to contribute, which can overcome the problems being faced, such as the application of blockchain in universities, namely how to use the blockchain system, what blockchain is, and how to change existing technology into disruptive technology. The experimental results state that by using data from the previous paper, the aim is to reveal the impact that blockchain technology has had on technology and information that is useful for improving the quality of universities in encouraging human potential and improving quality so that they can compete both domestically and abroad.